Multiplanar MRI imaging of sellar and parasellar lesions with clinical and pathological correlation - Karthikeyan, Vanchilingam; Ilanchezhian, Subramanyam (International Journal of Advances in Medicine, 2019)
Background: Sellar and parasellar/ juxtasellar regions are complex areas of the brain, hold delicate neurovascular structures. A number of diseases that affect the pituitary-hypothalamic axis can have profound clinical, endocrinological as well as neurological consequences. Aim of this retrospective study was to identify the MR imaging characteristics and epidemiology of sellar and suprasellar lesions, to correlate the MRI findings with histopathological findings and to highlight the diagnostic superiority of MR imaging. Methods: Author studied the records of 65 patients with sellar and suprasellar lesions for which preoperative MR imaging films or reports were available. Radiological appearances were correlated with intraoperative findings and post-operative histopathology. Results: Majority of patients in this study belonged to the age group 21-40 years. Most common mass lesion found was pituitary macroadenoma comprising 58% of the total cases. The accuracy of MRI in diagnosing macroadenomas are 96.80%. MR was 87.50%accurate, in diagnosing craniopharyngioma. MR was 100% in diagnosing meningioma in our study. Conclusions: MRI is the modality for characterizing sellar and suprasellar lesions, morphology of lesions, nature of contrast material enhancement and extent of lesions. Hence MRI is the modality of choice for diagnosing sellar and suprasellar masses with high accuracy